KONSTRUKSI KOMUNIKASI ANTAR PRIBADI KOMUNITAS SHARE&CARE DALAM MEMOTIVASI DIRI PENDERITA KANKER DI RUMAH SAKIT MURNI TEGUH MEDAN - Saranta Tassia Margareta Sitompul; Syafruddin Pohan (JURNAL SOCIAL OPINION: Jurnal Ilmiah Ilmu Komunikasi, 2020)
This study entitled "Construction of Interpersonal Communication Commuities Share & Care in Motivating Self Cancer Patients at Murni Teguh Hospital Medan" which aims at determining how interpersonal communication is formed among cancer sufferers as well as how the relationship between family support in self-motivation and knowing the psychological condition of the patient cancer in the Share & Care community. Interpersonal communication is an important instrument in approaching cancer sufferers, the Share & Care community in this case was born as a forum for them to provide motivation, enthusiasm and fight fear in undergoing treatment. Researchers used descriptive research methods, namely by collecting data through observations or observations, as well as managing information to then draw conclusions from the study. The number of informants taken was 5 informants who were members of the Share & Care community as well as cancer patients. This study resulted in a way of interpersonal communication carried out by members of the Share & Care community which had a positive effect on cancer patients, namely motivating themselves so that they were willing to follow the entire treatment process that had been determined by the doctor.